TEST DETERMINATION OF PROBABILITY OF AIRBORNE DETECTION OF GROUND SURFACE OBJECTS - S. V. Nikolaev (Научный вестник МГТУ ГА)
The article presents the methods, mathematical model and its software implementation for calculating the efficiency indicators of visual and hardware search and detection of ground objects from the aircraft. The methods differ from the known ones in that they use modern information technologies and are adapted to solve practical test problems. In addition, finding values of the visual detection probability of ground objects in full-scale experiments is unrealizable due to the huge amount of required expenses. The proposed method allows estimating a particular efficiency indicator of an aircraft when searching for ground objects in the flight tests – the yield on a generic object. The developed mathematical model takes into account the known range of object detection by its linear dimensions. The software implementation allows performing calculations for different values of the meteorological situation. The convergence of simulation results and flight experiments is estimated. To determine the convergence, the results obtained in real flight tests on proof ground with different meteorological conditions were compared with the results of calculations obtained by modeling. The relative discrepancy between the indicators obtained in the flight experiment and calculated by the developed program is less than 5%.The author proposes new private efficiency indicators for the visual detection task of typical ground objects. This is the area of possible detection of the ground object and the area of guaranteed access to it. These indicators allow performing a comparative assessment of the capabilities of aircraft to detect ground objects in tests. These indicators, unlike the known ones, have greater visibility and informational content.The developed computer program reduces the time spent by the tester on the calculation of indicators and the preparation of materials to the act by 3 times due to automation and usability. It allows us to perform calculations by varying any indicators on which the probability of detecting a typical ground object in the wide range of their change depends on.